Telaah Penafsiran Wahbah al-Zuḥaylī dalam al-Tafsīr al-Munīr tentang Penistaan Agama dalam al-Qur’ān - Nasiruddin Nasiruddin (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
The plurality of society, which consists of races, ethnicity, tribes, and religions, often generates a number of complex social problems such as harassment behavior against other different groups, including religious defamation. There have been Qur’anic verses which tell us how to deal with other groups who slandered Islam. Al-Qur’ān uses the terms al-istihzā’ and al-sukhrīyah most, when it discusses the issue. This article deliberates to discuss the issue of religious defamation focusing on Wahbah al-Zuḥaylī’s al-Tafsīr al-Munīr. To do so, the author will classify the relevant verses on the issue based on their asbāb al-nuzūl. The author will also find the relevant Ḥadīth to confirm the discussed matter. Al-Qur’ān has clearly informed us how to respond to those who commit religious defamation against Islam. It tells Muslims to not appoint them as leaders, not to support them when they are committing defamation with any means, and to advise them for their despicable deed.